2015
DOI: 10.4314/ijbcs.v9i2.47
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Polycyclic Aromatic Hydrocarbons (PAHs) in a tropical coastal lagoon (Grand-Lahou lagoon, Côte d’Ivoire)

Abstract: The distribution of 8 polycyclic aromatic hydrocarbons (PAHs) in the surface sediments of the GrandLahou lagoon (Côte d'Ivoire) was investigated using a high performance liquid chromatography (HPLC). The total concentrations of PAHs were between 1.55 and 437.52 µg/g in the dry season. Pyrene, benzo (b) fluoranthene and fluoranthene have the highest concentrations. In the rainy season, the total PAHs concentrations varied between 46.35 and 1222.73 µg/g. Pyrene, benzo (a) pyrene and benzo (a) anthracene were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
1
8
3
5
Order By: Relevance
“…D'une superficie terrestre de 322462 Km 2 , elle s'ouvre sur l'Océan Atlantique avec une zone côtière qui s'étend sur une superficie de 32 960 Km 2 . Elle est limitée au Nord par le Mali et le Burkina Faso, à l'Ouest par la Guinée et le Liberia, à l'Est par le Ghana et au Sud par l'Océan Atlantique selon Kouakou et al (2015).…”
Section: Introductionunclassified
“…D'une superficie terrestre de 322462 Km 2 , elle s'ouvre sur l'Océan Atlantique avec une zone côtière qui s'étend sur une superficie de 32 960 Km 2 . Elle est limitée au Nord par le Mali et le Burkina Faso, à l'Ouest par la Guinée et le Liberia, à l'Est par le Ghana et au Sud par l'Océan Atlantique selon Kouakou et al (2015).…”
Section: Introductionunclassified
“…Les paramètres suivants ont été déterminés (Kouadio et al, 2012) : -Le gain de poids (GP), exprimé en grammes (g). Il représente la différence entre le poids final Pf et le poids initial Pi des animaux.…”
Section: Mesure De La Prise Alimentaire Et Des Poidsunclassified
“…L'usage repose essentiellement sur la composition chimique du végétal (Muanda et al, 2011;Kouakou et al, 2015), mais justifié par la distribution des composés d'intérêt (Gueye et al, 2012 ). Comme bien d'autres organes végétaux, la racine tubéreuse de C. tinctorium n'est pas utilisée seulement comme aliment mais aussi comme organe végétal médicinal (Inngjerdingen et al, 2004 ;Song et al, 2011 ;Zhou et Qu, 2011).…”
Section: Introductionunclassified
“…And other hypothesis that I explain it in manuscript. I found lots of medicine that we can use it instead of chemicals one and have good research about scrupulous disease and I found some cures for specific diseases and I reached a point that it's about remedies that we can use it for our illness instead of some chemicals medicine [1]. Instead of medicine and medical science, I found the exact bones of our body (anatomy) and except these; I say some information about other fields of study and said it in my manuscript.…”
Section: Introductionmentioning
confidence: 99%